Asymmetric gradualism in US monetary policy - Knut Are Aastveit; Jamie Cross; Francesco Furlanetto; Herman K. van Dijk (Tinbergen Institute, 2024)
The Fed's policy rule shifts during different phases of the business cycle, particularly in relation to monetary easing and tightening phases. This finding is established through a dynamic mixture model, which estimates regime-dependent Taylor-type rules using US quarterly data from 1960 to 2021. This approach supports partitioning the data into two regimes corresponding to business cycle phases, closely linked to monetary easing and tightening. The estimated policy rule coefficients differ in two key ways between the regimes: the degree of gradualism is significantly higher during normal times than during recessions, when rates are typically cut; and the output gap coefficient is higher in the recessionary regime than in the normal regime. Notably, the estimate of the inflation coefficient satisfies the Taylor principle in both regimes. These results are further strengthened when using real-time data.
Keywords: C32; C51; E42; E52; E58; 330; Monetary policy; Taylor rules; mixed distributions; regime-switching